Social Media as informal learning agents for teenagers. Systematic review - Monreal-Guerrero, Inés María; Herrero Gozalo, Sara (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The purpose of this study is to carry out a systematic review of scientific publications regarding the state of the art of the role of social media as agents of informal musical education amongst teenagers. Nowadays, young people are advanced users of social media as a multimodal language. These, together with online video platforms, serve as a resource for their informal learning. However, after following the parameters of a PRISMA systematic review, this article establishes that there are scarce results of scientific literature delving into this topic.